Ultrasound prenatal diagnosis of nuchal cord with fetal asphyxia repercussion - Valladares, Elías (2015)
OBJECTIVE: To demonstrate that antepartum transabdominal ultrasound measurement of the depth and breadth of the cutout lace and the perpendicular distance from the midpoint of the notch to the fetal shell can predict the presence of nuchal cord asphyxia by neck in single fetuses term with vertex presentation. MATERIALS AND METHODS: In the Specialized Maternal Perinatal Institute between December 2002 and February 2003, an observational study of case-control in pregnant women with live term fetuses in vertex presentation without birth defects was performed. 120 pregnant women compared with suspected prenatal ultrasound fetal nuchal cord neck, confirmed the birth within 48 hours of the test, with 135 pregnant women without nuchal cord. RESULTS: Mean breadth and depth of the notch cord were 23.1 ± 5.9 mm and 8.3 mm of ± 2.9 SD), respectively. Measuring the perpendicular distance from the midpoint of the notch to the fetal shell was 12.1 ± 4.8 mm OF. The mean pH was 7.23 ± 0.45 in patients with suspected ultrasound confirmed nuchal cord at birth and 7.24 ± 0.72 in patients unused. No statistically significant difference (p> 0.05) was found. There was meconium relationship between birth and the presence of nuchal cord; p = 0.000001 (RR = 2.81; 95% CI 1.78 to 44.4) and between ± 7.20 pH and the presence of nuchal cord, with statistically significant difference; p = 0.002 (RR = 11.25; 95% CI 1.46 to 86.6). CONCLUSIONS: The depth of the notch cord was associated with ± 7.20 pH. To find a pH ± 7.20, the minimum notch depth should be 7.55 mm.